The Oil Wars Myth : Petroleum and the Causes of International Conflict - Meierding, Emily (Book collections on Project MUSE., 2020)
"The Oil Wars Myth challenges the popular belief that countries fight wars for oil resources by identifying overlooked obstacles to these conflicts and reexamining the presumed petroleum motives for many of the twentieth century's major international wars"--